Activated CD8 T-cell Hepatitis in Children With Indeterminate Acute Liver Failure: Results From a Multicenter Cohort. Issue 6 (December 2020) - Chapin, Catherine A.; Melin-Aldana, Hector; Kreiger, Portia A.; Burn, Thomas; Neighbors, Katie; Taylor, Sarah A.; Ostilla, Lorena; Wechsler, Joshua B.; Horslen, Simon P.; Leonis, Mike A.; Loomes, Kathleen M.; Behrens, Edward M.; et al.
ABSTRACT: Objectives: In many pediatric acute liver failure (PALF) cases, a diagnosis is not identified, and the etiology is indeterminate (IND-PALF). Our pilot study found dense CD8 T-cell infiltrates and increased T-cell clonality in liver specimens from IND-PALF patients. We aimed to validate these findings in a multicenter cohort with investigators blinded to diagnosis. Methods: PALF Study Group registry subjects with IND-PALF (n = 37) and known diagnoses (DX-PALF) (n = 18), ages 1 to 17 years, with archived liver tissue were included. Liver tissue slides were stained for T cells (CD8 and CD4), B cells (CD20), macrophages (CD163), perforin, and tissue resident-memory T cells (Trm, CD103), and scored as minimal, moderate, or dense. Lymphocytes were isolated from frozen liver tissue for T-cell receptor beta (TCRβ) sequencing. Results: Dense hepatic CD8 staining was found in significantly more IND-PALF (n = 29, 78%) compared with DX-PALF subjects (n = 5, 28%) ( P = 0.001). IND-PALF subjects were more likely to have dense or moderate perforin (88% vs 50%, P = 0.03) and CD103 (82% vs 40%, P = 0.02) staining compared with DX-PALF subjects. TCRβ sequencing of 15 IND-PALF cases demonstrated increased clonal overlap compared with 6 DX-PALF cases ( P = 0.002). Conclusions: Dense infiltration of effector Trm CD8 T cells characterizes liver tissue from IND-PALF subjects. Increased clonality suggests the T-cell expansion is antigen(s)-driven as opposed to a nonspecific inflammatory response. These findings support CD8 staining as a new biomarker of the activated CD8 T-cell PALF phenotype. Future studies are needed to characterize potential antigens, host risk factors, and inflammatory pathways with the goal of developing targeted therapies. Abstract : Supplemental Digital Content is available in the text